Drivers and Effects of Cryptic Invasion of Cornus sanguinea subsp. australis in Lithuania - Lukas Petrulaitis; Zigmantas Gudžinskas (Diversity, 2023)
Most alien plant species are usually discovered in new areas either immediately or within a relatively short period of time after their introduction. However, the introduction, spread, and invasion of some species go unnoticed for a long time. In Lithuania, such an alien plant is Cornus sanguinea subsp. australis, whose cryptic invasion has gone unnoticed due to its similarity to the native subsp. sanguinea. Cornus sanguinea subsp. australis is native to southeastern Europe and western Asia and is considered alien in other parts of Europe. This study, which was carried out between 2018 and 2022 in the territory of Lithuania, aimed to identify the distribution of the subsp. australis, as well as assess certain reproductive traits and its impact on the species diversity of the invaded communities. The results showed that the cryptic invasion of subsp. australis in Lithuania has been going on for several decades and is now well advanced. We found that the alien subspecies grows faster and that individuals in analogous habitats mature earlier than the native subsp. sanguinea. Furthermore, subsp. australis, compared to subsp. sanguinea, produces more flowers per inflorescence (84.0 ± 25.0 and 49.7 ± 20.9, respectively) and sets and ripens more fruits (25.6 ± 9.7 and 18.2 ± 7.6, respectively), which are among the most important factors for its further fast spread and invasion. The results of the vegetation analysis showed that the increase in abundance of both subspecies has a negative effect on species diversity in the community. However, the effect of the native subspecies on plant species diversity was negligible, while the effect of the alien subspecies was moderately negative and significant (r = −0.47; p < 0.05). Based on the results of the study, we can conclude that the alien subsp. australis performs better than the native subsp. sanguinea. Considering the current distribution and the drivers of dispersal, we suppose that subsp. australis will continue to spread rapidly in Lithuania and may pose a threat to the native subsp. sanguinea populations.